In-vitro Plant Regeneration in Celastrus paniculatus Willd.: An Endangered Medicinal Plant - Rahane, V. B.; Pawar, S. V.; Pawar, B. D.; Jadhav, A. S. (Indian Forester, 2016)
Celastrus paniculatus Willd., is an important medicinal plant. However, over exploitation of C. paniculatus has posed a serious threat to its existence. Therefore, in-vitro plant regeneration protocol was developed using nodal segment and shoot tip explants in Celastrus paniculatus Willd. Out of different explants nodal segment was found to be the most suitable for callus induction and further shoot regeneration. Highest callusing was obtained on MS medium supplemented with 1.0 mg/l BAP and 0.1 mg/l indole acetic acid (IAA). Earliest shoot initiation (10.6 days), highest per cent shoot multiplication (85.6%) and maximum number of shoots per explant (5) was observed in nodal segment explant on MS medium supplemented with 2.5 mg/l benzylaminopurine(BAP)and 0.5 mg/l thidiazuron (TDZ). Developed shoots were subjected to rooting on 1/2 MS medium with 1.5mg/l IBA(indole butyricacid)and the rooted plants were hardened in polycarbonated polyhouse.